The Effect of using Cartoon Film on Students’ English Vocabulry Mastery - Selly Ariska; M Khalid (Medan Resource Center, 2022)
This study aims to determine whether there is a significant effect of cartoon film media on the vocabulary of English students. This type of research is quantitative research and was conducted using two classes, the experimental class consisted of 30 students and the control class consisted of 30 students. In the data collection technique, the researcher used pre-test, treatment and post-test by giving a reading comprehension test consisting of 10 multiple choice items for each test. The results of this study indicate that there is a significant influence from the use of cartoon film media. This can be seen from the difference between the students’ mean scores from the pre-test and post-test in the experimental class which increased from 44 to 75. The average post-test score in the control class was 52 while the post-test score in the experimental class was 75. Higher than the average value of the control class. That means, the cartoon film media strategy can improve students’ understanding of English vocabulary.